2018
DOI: 10.1590/1678-4324-2018180134
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prolonged Salting on the Physicochemical Properties of Duck Egg White

Abstract: Salted duck eggs are unique among the important authentic foods of Thailand. They are mainly produced in Chaiya district, Surat Thani province, in the southern part of Thailand. The egg whites of salted duck eggs are normally unusable due to heavily salty taste upon prolonged storage. The present study was aimed to examine the foaming characteristics of egg white after being cured for a prolonged period (30 days). At 5-day intervals the egg whites were measured for salt, moisture, water activity, hydrophobicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This high salt level will induce cardiovascular diseases such as hypertension, 5 and change the quality of the salted egg white. For example, the cooked salted egg white is loose, not easy to peel, adhesive, and other conditions, 6 which reduces the eating quality of consumers and leads to a large number of salted egg white discarded in daily life 7 . The waste of egg white will cause economic losses and severe pollution of environmental and water sources after decomposition of rich protein resources fermentation in egg white 8…”
Section: Introductionmentioning
confidence: 99%
“…This high salt level will induce cardiovascular diseases such as hypertension, 5 and change the quality of the salted egg white. For example, the cooked salted egg white is loose, not easy to peel, adhesive, and other conditions, 6 which reduces the eating quality of consumers and leads to a large number of salted egg white discarded in daily life 7 . The waste of egg white will cause economic losses and severe pollution of environmental and water sources after decomposition of rich protein resources fermentation in egg white 8…”
Section: Introductionmentioning
confidence: 99%
“…Properties of these eggs depend on the length of curing with salt. More prolonged curing could improve the taste and structure of the egg yolk, which is the main component, as it has a wide range of applications and higher economic value than the egg white, which is frequently discarded owing to extreme saltiness; this leads to economic loss and an increase in waste and pollution (Venkatachalam, 2018;Wang, 2017;Xu et al, 2017). Therefore, food products made from salted duck egg white, while avoiding expensive desalination processes, have recently become popular (Xiao et al, 2019), resulting in several food products, including meringue, noodles, and jelly products.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the protein solubility, formability and emulsifying activity of salted duck egg albumen significantly decreased after 8 weeks of salting (Huang et al , ). Venkatachalam () noted that the yield stress which used as an important indicator of foam capacity increased from 32.33% to 70.55% due to duck egg salting. The textural characteristic of cooked salted egg albumen was correspondence to its viscosity which was governed by salting time and salt concentration (Xu et al , ).…”
Section: Introductionmentioning
confidence: 99%